Teaching English for Asking and Giving Opinion Learning Material through Cublak-Cublak Suweng Game - Elzahra, Hilda Rizqi (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2022)
During the learning process, students need something that is fun, easy to remember, and gives a good understanding of the material. In this case, teachers need to introduce fun learning innovations like games. Students have problems with learning English, especially in learning vocabulary. This study aims to find out how traditional cublak-cublak-suweng game procedures can be used as an effective way to help students learn English vocabulary. The research was conducted at MI Asy-Syafiiyyah 2 Brebes in 5th grade with a total of 24 students. The data were analyzed using quantitative and qualitative methods. The design of this study is classroom action research, covering four activities: planning, action, observation, and reflection. The result of the study showed that the cublak-cublak-suweng game can improve the student's vocabulary and recommend such materials to the student.